Constructions in Use - auf der Straße, Alexander (Dissertations in Language and Cognition, 2021)
Semantics is one of the core disciplines of philosophy of language. There are basically two strands of established theories: use-based and truth-conditional, with the latter being the dominant variety. This dominance has been questioned recently by linguists who embrace a research paradigm that is known as construction grammar. As construction grammar is use-based, it seems natural to suppose that its success is indirect support for use-based semantics in philosophy. This is true. But there's still a lot to do. Although there are use-based theories that fit quite well with current research in linguistics, they are far from being perfect. In particular, the most popular theory in that area is still tied to some of the main motivations behind truth-conditional semantics. 'Constructions in Use' offers an alternative by proposing to let this legacy go. Instead, it argues that philosophical semantics is best off if it goes for an entirely use-based theory.